Engineering Plasmonic Colloidal Meta‐Molecules for Tunable Photonic Supercrystals. Issue 20 (3rd August 2021) - Molet, Pau; Passarelli, Nicolás; Pérez, Luis A.; Scarabelli, Leonardo; Mihi, Agustín
Abstract: Ordered arrays of metal nanoparticles offer new opportunities to engineer light–matter interactions through the hybridization of Rayleigh anomalies and localized surface plasmons. The generated surface lattice resonances exhibit much higher quality factors compared to those observed in isolated metal nanostructures. Template‐induced colloidal self‐assembly has already shown a great potential for the scalable fabrication of 2D plasmonic meta‐molecule arrays, but the experimental challenge of controlling optical losses within the repeating units has so far prevented this approach to compete with more standard fabrication methods in the production of high‐quality factor resonances. In this manuscript, the optical properties of plasmonic arrays are investigated by varying the lattice parameter (between 200 and 600 nm) as well as the diameter of the gold colloidal building‐blocks (between 11 ± 1 and 98 ± 6 nm). It is systematically studied how the internal architecture of the repeating gold‐nanoparticle meta‐molecules influences the optical response of the plasmonic supercrystals. Combining both experimental measurements and simulations, it is demonstrated how, reducing the size of the gold nanoparticles it is possible to switch from strong near‐field plasmonic architectures to high‐quality factors (>60) for lattice plasmon resonances located in the visible spectral range. Abstract : Plasmonic supercrystals, ordered arrays of gold nanoparticles, are fabricated by template‐induced colloidal self‐assembly. Their optical properties are investigated by varying the lattice parameter (between 200 and 600 nm) as well as the diameter of the colloidal building blocks. Reducing the size of the gold nanoparticles is possible to switch from strong near‐field plasmonic architectures to high‐quality factor lattice plasmon resonances.